Interference analysis and radio frequency requirement of TD-LTE and LTE FDD systems - Jian FANG; Biao HUANG; Peichuan KANG; Ying XU (Dianxin kexue)
The system interference of 1.9 GHz TD-LTE and 1.8 GHz/2.1 GHz LTE FDD was studied. Firstly, the interference mechanisms and scenarios were analyzed, which focused on the interference of BS-BS. Moreover, the radio frequency requirements of TD-LTE and LTE FDD coexistence were given as the result of deterministic analysis and simulation calculations. The RF requirements were finally verified through lab tests as well as extensive field tests. The conclusion provides meaningful reference of 4G system utilization and BS coordination in China.